Graffiti e street art : verdade lúcida e dogma conveniente - Noronha, Miguel Alexandre Pires de, 1970- (2017)
For the last decades we have witnessed an artistic phenomenon on a global scale, which is particularly evident since the beginning of this millennium. It is characterized by interventions in urban environment, whether legal or illegal, using a variety of techniques and materials, predominantly in the fields of drawing and painting. A myriad of concepts, such as 'graffiti' and 'street art' among others, have been used in an attempt to define this phenomenon. These concepts are part of an already institutionalized and perhaps mystified narrative that presents these interventions as having been carried out in a spirit of rebellion, courage and transgression. However, a number of public and private institutions have sponsored events whose centrality resides precisely in so-called street art or graffiti, evoking their supposed critical intent and revolutionary potential in terms of political and social realities. In this context, there seems to be a general and fascinated acceptance of the image of urban artists as brave rebels who revolutionize the art world. However, if transgression is a marginal action in its nature, it seems impossible for it to become institutionally incorporated, since we know that the role of institutionalization is precisely to empty the unique character of events, presenting them as models for social behavior, turning them into integrated, standardized and repetitive practices. Thus, the obedient way of telling the story of disobedient artistic expressions is a hoax in which the authorized revolution, with a predetermined time and place, has been carried out by the writers, street artists or urban artists who are idolized as heroic criminals under the spotlight, but whose identity everyone knows, though pretending it's clandestine and transgressive. The subservience to the current historical narrative of graffiti, conceived with an exaggerated centrality in the USA, especially in New York, does not make sense. It leads us to forget the several historical moments before the official emergence of graffiti as it is presented today. It is inaccurate to overlook local particularities at the portuguese level, certainly rich in unique and decisive details, that form our own identity within contemporary street art, which deviate from that model. We are convinced that it is necessary to face critically the certainties that have been assumed as unquestionable, rejecting as absolute truths the reductive versions of the history of urban art. With this study we intend to verify the pertinence of the dominant discourse, unveiling the interests that support it. We will focus on concepts, techniques and historical facts, in a view that allows us to understand and demystify the intentionality of drawing in the public space within the framework of this artistic phenomenon. Our main goal is bringing up to light the lucid truths that oppose the convenient dogma